Reliability Analysis of 20kV Distribution System SRN 02 Transmission Line of PT PLN (Persero) UP3 Surakarta - Rifa'i, Muhammad; Kanata, Sabhan; Muntasiroh, Laily (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
PT. PLN (Persero) Customer Service Implementation Unit (UP3) Surakarta handles customer service and maintains distribution networks in smaller areas such as the SRN 02 Repeater. The repeater serves some areas in Sragen Regency which include agricultural areas, food centers and some industries. With the large number of consumers in SRN 02, making reliable electricity distribution such as the voltage supplied in accordance with the standard and reducing the number of blackouts due to interference. The methods used for reliability analysis are RIA and FMEA methods. Several indices are analyzed, namely the average failure frequency or SAIFI, the average outage frequency or SAIDI, the average customer outage frequency or CAIDI and the frequency of interference to customers or CAIFI. The results of the calculation of the reliability index of SRN 02 in 2023 RIA method for SAIFI 7,256 times / year, SAIDI 21,906 hours / year, CAIDI 3,018 hours / year, and CAIFI 0.325 times / year. While the calculation results with the FMEA method for SAIFI 0.016 times / year, SAIDI 0.487 hours / year, CAIDI 29,609 hours / year, and CAIFI 0.033 times / year. The results of the calculation of SAIFI and SAIDI in the RIA method are not normal in accordance with SPLN 68-2: 1986. While the results of SAIFI and SAIDI calculations in the FMEA method are normal in accordance with SPLN 68-2: 1986.PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Surakarta menangani layanan pelanggan dan menjaga jaringan distribusi di wilayah yang lebih kecil seperti pada Penyulang SRN 02. Penyulang tersebut melayani sebagian wilayah di Kabupaten Sragen yang meliputi wilayah pertanian, pusat pangan dan sebagian industri. Dengan banyaknya jumlah konsumen pada Penyulang SRN 02, membuat penyaluran listrik yang handal seperti tegangan yang disalurkan sesuai dengan standar dan berkurangnya jumlah pemadaman akibat gangguan. Metode yang digunakan untuk analisis keandalan yaitu metode RIA dan FMEA. Beberapa indeks yang dilakukan analisis yaitu frekuensi kegagalan rata-rata atau SAIFI, frekuensi pemadaman rata-rata atau SAIDI, frekuensi pemadaman rata-rata pelanggan atau CAIDI dan frekuensi gangguan pada pelanggan atau CAIFI. Hasil perhitungan indeks keandalan Penyulang SRN 02 tahun 2023 metode RIA untuk SAIFI 7.256 kali/tahun, SAIDI 21.906 jam/tahun, CAIDI 3.018 jam/tahun, dan CAIFI 0.325 kali/tahun. Sedangkan hasil perhitungan dengan metode FMEA untuk SAIFI 0.016 kali/tahun, SAIDI 0.487 jam/tahun, CAIDI 29.609 jam/tahun, dan CAIFI 0.033 kali/tahun. Hasil perhitungan SAIFI dan SAIDI pada metode RIA tidak normal sesuai dengan SPLN 68-2:1986. Sedangkan hasil perhitungan SAIFI dan SAIDI pada metode FMEA normal sesuai dengan SPLN 68-2:1986.